What do lead banks learn from leveraged loan investors? - Max Bruche; Ralf R. Meisenzahl; David Xiaoyu Xu (Federal Reserve Bank of Chicago, 2023)
In leveraged loan deals, lead banks use bookbuilding to extract pricerelevant information from syndicate participants. This paper examines the content of such information. We find that pricing adjustments during bookbuilding are highly informative, not only about investors' required risk premium but also about borrower quality. A one-percentage-point increase in loan spread predicts a 0.8% higher excess return, a proxy for risk premium, over the first 3 months of secondary market trading. More importantly, it also predicts a 3% higher probability of subsequent default, implying that investors have private information about borrower quality that is unknown to the lead bank. Our findings suggest a new view of how information asymmetries affect syndicated lending.
Keywords: G23; G24; G30; 330; syndicated loans; leveraged loans; underwriting